Effect of Intraperitoneal versus Oral Drench of Beta-Amino Butyric Acid on Platelets in Sprague Dawley Rats - Mustafa Salah Hasan (Journal of Global Pharma Technology, 2020)
To study the effect of oral and injected BABA on platelet production this study was done, The first group (intra peritoneal injection group): This group consisted of 20 animals given (BABA) after dilution with 2 ml distilled water by intra peritoneal injection for four weeks, this group was divided according to BABA concentration into three secondary groups (5 animals per group): first concentration (1g/ kg), second concentration (0.5 g / kg), third concentration (0.25 g / kg) and control group was injected with distilled water 2 ml once a week for four weeks, The second group (orally drenching group): This group included 20 animals also given the substance (BABA) at the same concentrations and doses of the first group at the same time using oral route. Keywords: BABA, Rat, Platelets.